Analysis of The Influence of Fundamental and Macroeconomic Factors on Stock Prices in Energy Sector Companies Listed on The Indonesia Stock Exchange - Ilham Dicardo; Mohamad Adam; Marlina Widiyanti; Isni Andriana (Jurnal Syntax Transformation, 2023)
This study aims to test and provide evidence of the influence of macro fundamental factors, namely Liquidity (CR), Solvency (DER), Profitability (ROE), Valuation (PBV), inflation, and interest rates on stock prices (PER) in energy sector companies listed on the Indonesia Stock Exchange. This study uses the purposive sampling method conducted on energy sector companies on the Indonesia Stock Exchange for the 2018-2022 period as many as 10 companies. The type of data used is quantitative data in the form of financial data sourced from annual financial statements. The analysis method used in the study was regression analysis of panel data with the Eviews 12 application tool. Based on the method tested using the Model Feasibility Test (Test F), it can be concluded that this research model is feasible to use. The results of the analysis show that Solvency (DER) affects stock prices, while Liquidity (CR), Profitability (ROE), Valuation (PBV), inflation and interest rates do not affect share prices in energy sector companies on the Indonesia Stock Exchange.